Examination of the angle position on the cone dispenser - Hagymássy, Zoltán (Acta Agraria Debreceniensis, 2007)
The most important distributing construction of small plot seed-drills and fertiliser dispensers is the cone dispenser. The cone dispenser can operate based on simple gravity or with an Oyjord-type cone-cell or Hege-type cone-belt structure. The unevenness of spreading of each type is significantly influenced by the aberration of the vertical angle position of the cone dispenser. An approximate method was improved modelling of the fault of the cone dispenser. In my article, I will provide information about the essence of the model and its derivations. On the model, I cover the cone piston with a theoretical net and at random scale between each scale interval I count the forces acting on the grain and the movement of the grain. If I set the scale of the net close enough, with good proximity, I get the whole orbit. The unevenness of dispensing can be calculated from the position of the grains getting to the bottom of the cone in case of different geometric data. My measurements imply that an approximate method is able to model both the tendency and the value of the deviation caused by the fault of the angle position. Both the theoretical model and the measurement prove that 2-3° deviation results in significant change in the unevenness of dispensing.